The panorama of translations of Brazilian and Portuguese literature into the Slovene language (1991–2018) - Medvedsek, Mojca; Pograjc, Blažka Müller (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2018)
The first translations from Portuguese into Slovene appeared in the twentieth century. Most of the translations were published after the Second World War when Slovenia was still part of the Socialist Federative Republic of Yugoslavia and was integrated in a much larger and linguistically diverse cultural territory. The article presents the historical panorama of translations of Brazilian and Portuguese literature into Slovene, highlighting the history of the last twenty-seven years following the independence of Slovenia – i.e. from 1991 onwards. ————————————————————————————— O PANORAMA DAS TRADUÇÕES LITERÁRIAS DE LITERATURA PORTUGUESA NA ESLOVÊNIA (1991-2018) As primeiras traduções de literatura portuguesa para o esloveno apareceram no século XX. A maioria das traduções foi publicada após a segunda guerra mundial, quando a Eslovênia ainda fazia parte da República Federativa Socialista da Iugoslávia e era parte de um território cultural muito maior e linguisticamente diverso. O artigo apresentará o panorama histórico das traduções eslovenas da literatura brasileira e portuguesa para a língua eslovena, destacando a história dos últimos vinte anos após a independência da Eslovênia, ou seja a partir de1991. — Original em inglês.